Information, motivation and behavioral skills associated with condom use in the last sexual intercourse in males deprived of freedom - Sánchez Medina, Ricardo (2019)
This study aimed to analyze the differences in condom use with respect to the level of information about HIV, and the motivation and behavioral skills to use condoms in males deprived of freedom from three age strata. A total of 1,104 males belonging to long-term pretrial detention facilities for adolescents (comunidades de diagnóstico) and a social rehabilitation center in Mexico City were evaluated. They were divided into three groups using as criteria the distribution assigned by age quartiles, as well as the comparison between those who used and those who did not use a condom in their last sexual intercourse. A 3x2 factorial analysis was carried out and differences were found regarding the level of information and behavioral skills in relation to the age groups and condom use; however, there were no significant differences in the motivation. The results are discussed in terms of the importance of designing intervention programs for males deprived of freedom  considering how the experience is related to the use of condoms in sexual intercourse.